1981
DOI: 10.1099/00221287-127-2-391
|View full text |Cite
|
Sign up to set email alerts
|

Proline Uptake in Candida albicans

Abstract: 391~ L-Proline entered both mycelial and yeast cells of Candida albicans by an active transport system of high specificity at low ((0.1 mM) external concentrations of substrate. The apparent K, value of this system was 0-1 mM for both types of cells, while the Vvalue was 4 nmol min-' (mg dry wt)-' for mycelial cells and 1-4 nmol min-l (mg dry wt)-' for yeast cells. At L-proline concentrations greater than 0-1 mM, the amino acid appeared to enter both morphological forms by diffusion as well as active transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
5
26
0
Order By: Relevance
“…Characterization of the proline uptake system showed it to be constitutive, as found by Dabrowa & Howard (1981) and Jayakumar et al (1979), specific, confirming the results of Dabrowa & Howard (1981), and partially inducible in that preincubation in proline increased uptake, a finding also reported by Jayakumar et al (1979). We also found that proline uptake was subject to ammonium repression; removal of nitrogen from the medium resulted in an increase of the proline uptake rate in both the presence and absence of glucose.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Characterization of the proline uptake system showed it to be constitutive, as found by Dabrowa & Howard (1981) and Jayakumar et al (1979), specific, confirming the results of Dabrowa & Howard (1981), and partially inducible in that preincubation in proline increased uptake, a finding also reported by Jayakumar et al (1979). We also found that proline uptake was subject to ammonium repression; removal of nitrogen from the medium resulted in an increase of the proline uptake rate in both the presence and absence of glucose.…”
Section: Discussionsupporting
confidence: 72%
“…Verma & Prasad (1983) found no evidence for ammonium repression of the uptake of a number of amino acids or the imino acid proline in C. albicans, but it has been demonstrated in S. chevalieri , S. cerevisiae (Lasko & Brandriss, 1981) and Aspergillus nidulans (Arst et al, 1980). The difference in uptake rates between yeast and mycelial cells found by Dabrowa & Howard (1981) may have reflected derepression occurring in the mycelial cultures before the uptake determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast forms were grown in yeast extract peptone dextrose (YPD) or a yeast nitrogen base containing 50 mM glucose (YNB) (66). Mass conversion of stationary-phase yeasts (grown at 30°C for 48 h) to germ tubes was induced at 37°C in the following prewarmed media: Lee's (pH 6.8) (45), medium 199 (Gibco-BRL) with 150 mM HEPES (pH 7.0) (M199), M199 containing 5% bovine calf serum (Sigma) (M199ϩserum), 50 mM potassium phosphate (pH 6.0) plus 10% bovine calf serum (23), and 10 mM imidazole-HCl buffer (pH 7.0) containing 0.2 mM MnCl 2 (with the following inducing agents: 4 mM N-acetylglucosamine, 10 mM L-proline plus 10 mM glucose, or 2.5 mM glutamine plus 2.5 mM glucose) (18,49,71). Whole human saliva was collected on ice and clarified by centrifugation at 10,000 ϫ g for 15 min at 4°C (37).…”
Section: Methodsmentioning
confidence: 99%
“…These types of morphologies have distinct abilities to adhere, proliferate, invade, or escape phagocytic cells and, therefore, contribute by different degrees to the pathogenesis of the infection. The transfer from the yeast form to the filamentous form of growth is induced by certain chemicals (14,18,20,48), a temperature close to 37°C (30), and a neutral pH (49), while chlamydospore formation is induced in vitro under special conditions, such as a low concentration of glucose, darkness, low temperature (24 to 28°C) and microaerophilia.The molecular mechanisms involved in the regulation of polymorphism in C. albicans are very complex. Genetic analysis has shown the implication of several genes and regulatory cascades in this process (31,37,54,56).…”
mentioning
confidence: 99%